2007
DOI: 10.1002/jsl.36
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐oxidative stability of ionic liquids as lubricating fluids

Abstract: Thermo-oxidative stability of ionic liquids was evaluated by three bulk-scale tests. The changes in chemical and physical properties such as viscosity, deposit formation, weight loss and TAN were obtained. The results are discussed in terms of chemical structure of ionic liquids. TFSI derivatives exhibit good thermo-oxidative stability in comparison with BF4 derivatives. As chain length of alkyl group in imidazolium-cationic moiety increases, the thermo-oxidative stability of the molecule decreases. Water cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 27 publications
(37 reference statements)
0
43
0
Order By: Relevance
“…ILs have a number of properties that make them suitable as prospective lubricants; firstly, their low volatility, low flammability and thermal stability means they are able to safely withstand increased temperatures and pressure involved when there is high friction. In fact, Minami et al have shown a series of imidazolium and ammonium ILs to have a considerably higher stability than a conventional synthetic oil at 200 °C [12].…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…ILs have a number of properties that make them suitable as prospective lubricants; firstly, their low volatility, low flammability and thermal stability means they are able to safely withstand increased temperatures and pressure involved when there is high friction. In fact, Minami et al have shown a series of imidazolium and ammonium ILs to have a considerably higher stability than a conventional synthetic oil at 200 °C [12].…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…It is known in literature that bis(trifl uoromethylsulfonyl)-imide as anion for ionic liquids leads to more thermo-oxidative and physical advantages. 14,15 Many investigations in AC²T research showed also tribological advantages of this anion compared to other anions, e.g. BF 4 and PF 6 .…”
Section: Specimens Selectedmentioning
confidence: 99%
“…Further, hydrophobic anions afford a superior thermo-oxidative stability to RT-ILs as compared to hydrophilic ones [12,14]. The thermo-oxidative stability of RT-ILs decreases with increase in the chain length of the alkyl group in an imidazolium cation [15].…”
Section: Introductionmentioning
confidence: 99%